The Cell Wall Deacetylases Spy1094 and Spy1370 Contribute to Streptococcus pyogenes Virulence - Tiger Aspell; Adrina Hema J. Khemlani; Catherine Jia-Yun Tsai; Jacelyn Mei San Loh; Thomas Proft (Microorganisms, 2023)
Streptococcus pyogenes, or Group A Streptococcus (GAS), is a strictly human pathogen that causes a wide range of diseases, including skin and soft tissue infections, toxic shock syndrome and acute rheumatic fever. We have recently reported that Spy1094 and Spy1370 of S. pyogenes serotype M1 are N-acetylglucosamine (GlcNAc) deacetylases. We have generated spy1094 and spy1370 gene deletion mutants in S. pyogenes and gain-of-function mutants in Lactococcus lactis. Similar to other cell wall deacetylases, our results show that Spy1094 and Spy1370 confer lysozyme-resistance. Furthermore, deletion of the genes decreased S. pyogenes virulence in a human whole blood killing assay and a Galleria mellonella (Greater wax moth) larvae infection model. Expression of the two genes in L. lactis resulted in increased lysozyme resistance and survival in whole human blood, and reduced survival of infected G. mellonella larvae. Deletion of the spy1370, but not the spy1094 gene, decreased resistance to the cationic antimicrobial peptide cecropin B, whereas both enzymes increased biofilm formation, probably resulting from the increase in positive charges due to deacetylation of the cell wall. In conclusion, Spy1094 and Spy1370 are important S. pyogenes virulence factors and might represent attractive targets for the development of antibacterial agents.